Harmonized system of quality assessment for electronic components. Semiconductor devices. Integrated circuits. Sectional specification for film integrated circuits and hybrid film integrated circuits on the basis of the qualification approval procedures. (15th August 1997) - British Standards Institution,
No abstract available